On the Exploitation of Lignin Slow Pyrolysis Products - Guido Busca; Elena Spennati; Matteo Borella; Alessandro A. Casazza; Gabriella Garbarino (Energies)
The potential of technical lignins as secondary raw materials is discussed. The characteristics of lignin pyrolysis, with particular emphasis on slow pyrolysis technologies, are briefly summarized. The slow pyrolysis process, which can be self-sustained by burning the coproduced gas, can primarily produce high-quality biochar in significant amounts, to be used as a fuel, as a reductant in metallurgy, and as an adsorbent and catalyst component. Together, significant amounts of bio-oil can be produced, rich in guaiacols, which are commercial and expensive chemicals produced today via petrochemical routes and used in pharmacology, food chemistry, polymer chemistry, etc. Such compounds, or bio-oil itself, can also be converted by hydrodeoxygenation into biofuels. A possible simplified flowsheet for a lignin slow pyrolysis process in the frame of a ligneocellulosics-based biorefinery is proposed.